National Hospital Ambulatory Medical Care Survey, 2006 ([Verlag nicht ermittelbar], 2010)
The National Hospital Ambulatory Medical Care Survey (NHAMCS) provides data from samples of patient records selected from emergency departments (EDs) and outpatient departments (OPDs) of a national sample of hospitals. The resulting national estimates describe the use of hospital ambulatory medical care services in the United States. For the 2006 survey, data were collected from 236 OPDs and 464 EDs. Among the variables included are age, race, and sex of the patient, reason for the visit, physician's diagnoses, cause of injury, surgical procedures (OPDs only), medication therapy, and expected source of payment. For 2006, additional updates and revisions have been made to both the emergency department and outpatient department data, including modifications to pre-existing variables and the inclusion of new variables pertaining but not limited to electronic medical record systems and diagnostic screening services.